Development of diagnostic SNP markers for quality assurance and control in sweetpotato (Ipomoea batatas (L.) Lam.) breeding programs - Gemenet, D.; Kitavi, M.; David, M.; Ndege, D.; Ssali, R.T.; Swanckaert, J.; Makunde, G.S.; Yencho, George Craig; Grüneberg, W.J.; Carey, E.E.; Mwanga, Robert O.M.; Andrade, M.I.; et al. (Public Library of Science, 2020)
Quality assurance and control (QA/QC) is an essential element of a breeding program’s optimization efforts towards increased genetic gains. Due to auto-hexaploid genome complexity, a low-cost marker platform for routine QA/QC in sweetpotato breeding programs is still unavailable. We used 662 parents of the International Potato Center (CIP)’s global breeding program spanning Peru, Uganda, Mozambique and Ghana, to develop a low-density highly informative single nucleotide polymorphism (SNP) marker set to be deployed for routine QA/QC. Segregation of the selected 30 SNPs (two SNPs per base chromosome) in a recombined breeding population was evaluated using 282 progeny from some of the parents above. The progeny were replicated from in-vitro, screenhouse and field, and the selected SNP-set was confirmed to identify relatively similar mislabeling error rates as a high density SNP-set of 10,159 markers. Six additional trait-specific markers were added to the selected SNP set from previous quantitative trait loci mapping studies. The 36-SNP set will be deployed for QA/QC in breeding pipelines and in fingerprinting of advanced clones or released varieties to monitor genetic gains in famers’ fields. The study also enabled evaluation of CIP’s global breeding population structure and the effect of some of the most devastating stresses like sweetpotato virus disease on genetic variation management. These results will inform future deployment of genomic selection in sweetpotato.